Less is more - R. Alayón; A. Canalda; R. Albertini; J.M. De Gomar; N. Moro (European Psychiatry, 2022)
Introduction Very few research about atrioventricular blocks (AVB) and use of antipsychotic drugs has been made, although it may play an important role in the outcome of any patient affected by psychosis and AVB.